2005
DOI: 10.1115/1.2130732
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Catalytic Regeneration Modeling of SiC Diesel Particulate Filters

Abstract: Increasingly stringent diesel particulate emissions standards have reestablished international interest in diesel filters, whose first series application dates back to 1985. Modern diesel engine technology, with computerized engine management systems and advanced, common rail injection systems, needs to be fully exploited to support efficient and durable diesel filter systems with catalytic aids, as standard equipment in passenger cars. Efficient system and components’ optimization requires the use of mathemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Specifically, within the last decades engine emissions have been reduced significantly adopting new aftertreatment strategies [1][2][3][4][5]. To this purpose, a host of investigations has been focused on oxidation catalysts (OC), diesel particulate filters (DPF), lean NO x traps (LNT), lean NO x catalysts (LNC), and selective catalytic reductions (SCR) [6][7][8][9][10][11][12]. Nevertheless, further improvements are necessary to meet the more and more stringent exhaust regulations, to improve the energetic effectiveness of modern emission control systems and to balance costs and fuel economy benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, within the last decades engine emissions have been reduced significantly adopting new aftertreatment strategies [1][2][3][4][5]. To this purpose, a host of investigations has been focused on oxidation catalysts (OC), diesel particulate filters (DPF), lean NO x traps (LNT), lean NO x catalysts (LNC), and selective catalytic reductions (SCR) [6][7][8][9][10][11][12]. Nevertheless, further improvements are necessary to meet the more and more stringent exhaust regulations, to improve the energetic effectiveness of modern emission control systems and to balance costs and fuel economy benefits.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few decades a host of experimental and numerical investigations have been carried out to increase the efficiency of aftertreatment systems and reduce engine tail pipe emissions [7][8][9][10][11][12]. Attention has been mainly focused on three-way catalysts (TWCs), oxidation catalysts (OCs), diesel particulate filters (DPFs), lean NO x traps (LNTs), lean NO x catalysts (LNCs) and selective catalytic reductions (SCRs) [13][14][15][16][17]. Specifically, a host of investigations demonstrated that, for stoichiometric spark ignition engines, three-way catalytic converters represent a proper and efficient method to control the pollutant emissions, as can be found in literature [7,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Also the asymptotic solution predicts well the numerical solution. Table 1: Thermophysical properties used in the analysis and numerical computation c m (J/kg K) 1100 [31] c g (J/kg K) 1007 [44] λ g (W/m K) 0.026 [44] ρ m (kg/m 3 ) 1300 [31] ρ g (kg/m 3 ) 1.187 [44] Q (J/kg) 3.0×10 7 [31] A (kg/m 3 s) 1.2×10 11 [32] …”
Section: Validation Of the Asymptotic Analysismentioning
confidence: 99%
“…We observe that in some processes combustion occurs with the active participation of the combustible porous medium, while in some cases combustion happens considering the same temperature of the phases or, use numerical computations to present their final results. On the other hand, numerous computational studies [23][24][25][26][27][28][29][30][31][32][33] have been published to understand the regeneration process of diesel particulate filters. Even though the models are sophisticated with many degrees of freedom but they require detailed input data such as exhaust gas velocity profiles or complex reaction kinetics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation